2021
DOI: 10.3390/life11101056
|View full text |Cite
|
Sign up to set email alerts
|

Depressive and Neurocognitive Disorders in the Context of the Inflammatory Background of COVID-19

Abstract: The dysfunctional effects of the coronavirus disease 2019 (COVID-19) infection on the nervous system are established. The manifestation of neuropsychiatric symptoms during and after infection is influenced by the neuroinvasive and neurotrophic properties of SARS-CoV-2 as well as strong inflammation characterised by a specific “cytokine storm”. Research suggests that a strong immune response to a SARS-CoV-2 infection and psychological stressors related to the pandemic may cause chronic inflammatory processes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 211 publications
(363 reference statements)
0
21
0
Order By: Relevance
“…Previous studies have suggested that the contribution of COVID-19 to the increased prevalence of depression has been attributed to population shocks, social isolation, quarantines and uncertainty about the future (60). It has also been suggested that the association of COVID-19 with depression is inextricably linked to neuroinflammation (61,62). da Silva Lopes L et al noted that due to the action of inflammatory cytokines and the presence of cell surface ACE-2 receptors, COVID-19 survivors may be more susceptible to depression (63).…”
Section: Frontiers Of Researchmentioning
confidence: 99%
“…Previous studies have suggested that the contribution of COVID-19 to the increased prevalence of depression has been attributed to population shocks, social isolation, quarantines and uncertainty about the future (60). It has also been suggested that the association of COVID-19 with depression is inextricably linked to neuroinflammation (61,62). da Silva Lopes L et al noted that due to the action of inflammatory cytokines and the presence of cell surface ACE-2 receptors, COVID-19 survivors may be more susceptible to depression (63).…”
Section: Frontiers Of Researchmentioning
confidence: 99%
“…Results of this study are therefore probably partially related to the antidepressant effect of fluoxetine and are not necessarily linked to the COVID-19 pathology itself. Overall, in a clinical context, the improvement of depression and anxiety should be considered an important confounder in relation to somatic improvement, because psychiatric improvement has been shown to have a direct effect on somatic endpoints [ 55 , 56 ]. Therefore, changes in depressive and anxiety symptoms should also be screened in future studies assessing the effectiveness of antidepressants in COVID-19 patients, making the control of this cofactor possible.…”
Section: Clinical Evidence For the Potential Benefits Of Using Fluoxe...mentioning
confidence: 99%
“…However, newer data suggests that the indication for antidepressants should be re-examined ( Wada et al, 2001 ), as fluoxetine, sertraline and venlafaxine have been successfully used in various case reports ( Dubovsky et al, 2012 ). Fluoxetine, in particular, has been shown to be a promising drug in the context of Covid-19 due to reported anti-inflammatory properties ( Dąbrowska, Galińska-Skok, & Waszkiewicz, 2021 ). TCAs like nortriptyline and desipramine have been labeled as “likely efficacious” and “clinically useful” to treat depression in PwP ( Seppi et al, 2019 ) and could be considered also for anxiety in PD, although they should be avoided in patients with suicidal ideation or cardiovascular problems ( Prediger, Matheus, Schwarzbold, Lima, & Vital, 2012 ).…”
Section: Moderate Covid-19 Infectionmentioning
confidence: 99%